Interaction of magnetospheric Alfvén waves with the ionosphere in the Pc1 frequency band. Issue 1 (25th January 2016) - Fedorov, E.; Mazur, N.; Pilipenko, V.; Engebretson, M.
Abstract: A characteristic feature of the upper ionosphere is the occurrence of the ionospheric Alfvén resonator (IAR) and MHD waveguide, which can trap electromagnetic wave energy in the range from fractions of a Hz to a few Hz. This wave trapping ensures the strong dependence of the ionospheric transmission/reflective properties on frequency. We have developed a numerical model of the magnetospheric Alfvén wave interaction with the ionosphere and transmission to the ground based on the solution of multifluid magnetohydrodynamic (MHD) full wave equations in a realistic ionosphere, whose parameters were reconstructed from the International Reference Ionosphere model. The MHD modes are coupled owing to the frequency‐dependent Hall conductivity and geomagnetic field line inclination. This model can be applied to the interpretation of the spectral structure of electromagnetic emissions of the magnetospheric origin in the band 0.1–10 Hz observed at various latitudes. The model predicts that the upper part of the ULF spectrum ( f > 1 Hz) will be severely absorbed upon wave transmission through the daytime ionosphere to the ground. At nighttime the transmission coefficient of Alfvén waves has an oscillatory dependence on frequency, with "transmission windows" at the lowest IAR eigenfrequencies (<3 Hz). At higher frequencies (3–10 Hz) the reflection/transmission coefficients are dominated by periodic scale‐dependent modulation owing to the waveguide modes. Broad maxima/minima of the transmission coefficient are determined by the phasing between Alfvén and fast magnetosonic waves at the bottom of the ionosphere. Key Points: Model based on coupled MHD equations in IRI ionosphere developed IAR and FMS waveguide ensure oscillatory scale‐dependent ULF wave transmission At nighttime transmission of large‐scale Alfven waves has broad window 5–7 Hz